Answer:
In the Pascal Expansion of
the third term is
.
Explanation:
Here, the given expression is given as
![(x+3)^4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g65rtpm4i82wcilg5sdg9bkgp9ug641hda.png)
Now, by the PASCAL'S TRIANGLE EXPANSION:
![(a + b)^4 = 1(a)^4 + 4(a)^3b + 6(a)^2b^2 + 4(a)b^3 + 1b^4\\= 1 + 4b + 6a^2 + 4b^3 + b^4.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8genkih7rfezkcr7x8358zt23gce1lg28l.png)
Substituting a = x and b = 3, we get:
![(x + 3)^4 = 1(x)^4 + 4(x)^3(3) + 6(x)^2(3)^2 + 4(x)(3)^3 + 1(3)^4\\= x^4 + 12x^3 + 54x^2 + 108x+ 81](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qjg61laxtrijm0p03vl2ik53sqrqv7k7rb.png)
In the given expansion, the third term is
.
Hence, in the Pascal Expansion of
the third term is
.